Acoustical Characteristics Evaluation of Japanese Glottal Stops - MICHI, Kenichi; WANG, Gonting; TAKAHASHI, Koji; WAKUMOTO, Masahiko (Journal of Japanese Cleft Palate Association, 1991)
To quantitatively evaluate the acoustic characteristics of Japanese glottal stops (JGS), pronounciation of /ta/ and /ka/ in 10 normal subjects and 14 patients with cleft palates including congenital velophargnyeal incompetence and functional articulation disorders were analyzed by sound spectrography (SG) and microcomputer. The frequency and time domain of both target syllables obtained were compared with psycho-acoustical judgment by speech therapists. The conclusions were as follows: 1. SG analysis showed that voice onset time (VOT) in the pronunciation of patients with articulation disorders were observed to be shorter than those of normal subjects. Spectrogram pattern in 1/3 of the JGS samples showed irregular fills, which were recongized when producing the fricative consonants, following obliteration of formant components in vowels. 2. Computer acoustical analysis showed: 1) Spectral envelope score (SES), which quantitated consonant frequency characters in spectrum envelope, demonstrated that the number of samples with a value above 5 dB in the control group was 60 % during the normal articulation of /ta/. In the test group we observed 17∼37 % JGS of /ta/ and /ka/, as well as normal articulation of /ka/. 2) VOT of more than 20 msec in all normal articulations of /ka/ with an average time of 44.6 msec, whereas 23∼41 % in normal articulation of /ta/ and JGS of /ta/ and /ka/ demonstrated an average time of 17.2∼20.8 msec.3) (ΔF2-ΔF 3) which is the difference in the transient portion calculated by linear predictive coding (LPC) method that showed that more than 200 Hz were 63 % in normal articulation of /ta/, whereas 13∼19 % in JGS of /ta/ and /ka/ and normal articulation of /ka/. 3. Psycho-acoustical judgment evaluating both the degree of distortion and clarity of burst which are the characteristics of JGS had been statistically compared with the results of computer acoustical analysis by rank correlation coefficicient method. The inverse correlationship between VOT and the psyco-acoustical judgment for the degree of distortion was demonstrated to be statistically significant.